Studi Eksperimental Hubungan Parameter Proses Pemesinan Wire EDM dengan Kekerasan Permukaan untuk Material AISI 1148 - Martowibowo, Sigit Yoewono; Pinandito, Satrio (Mesin, 2000)
Technology development advances in recent years produce materials having higher strength, complicated shape and high accuracy. These have placed demands on the new technology in machining processes. Non-conventional machining processes are providing effective solutions to the problem mentioned above.Wire EDM machining is one of some non-conventional machining processes which is using wire as tool. The limitation of this technique as also happened with other non-conventional machining processes is a lower rate of material removal comparing to the conventional processes.This study was conducted to obtain data in order to optimize machining condition of medium carbon steel using for die material.